The use of computational fluid dynamic technique in ship control design. (2nd January 2021) - Martelli, M.; Villa, D.; Viviani, M.; Donnarumma, S.; Figari, M.
ABSTRACT: This paper presents a methodology to develop the control systems of a surface vessel by using both computational fluid dynamics techniques and model-based control design. The model-based control design is supported by a simulation platform where both the ship hydrodynamics and the propulsion plant are modelled together. The application of CFD is related to the direct evaluation of the hull forces in the ship hydrodynamic model, for different manoeuvring conditions. The developed design tool is essential in the preliminary design phase, as a benchmark to test the control algorithms for autonomous ships. The comparison between numerical assessment and regression-based formulae has been performed on non-standard manoeuvres to quantify the difference in thrust allocation from the point of view of control design. Eventually, to validate the effectiveness of the proposed methodology, the results of the sea trials for different manoeuvres are shown.